Ready to go 3D? A semi-automated protocol for microwell spheroid arrays to increase scalability and throughput of 3D cell culture testing - Basu, Amrita; Dydowiczová, Aneta; Trosko, James E; Bláha, Luděk; Babica, Pavel (Toxicology mechanisms and methods, 2020)
3-dimensional (3D) cell cultures are being increasingly recognized as physiologically more relevant in vitro models than traditional monolayer cultures, because they better mimic in vivo-like microenvironment, cell-cell and cell-extracellular matrix interactions. Nevertheless, the broader use of 3D models might be limited by requirements for special consumables, equipment, or skills for 3D cell cultures, and by their limited throughput and scalability. In this study, we optimized and adapted a commercially available agarose-micromolding technique to produce scaffold-free spheroid cultures. Brightfield microscopy was used for routine nondestructive and noninvasive evaluation of spheroid formation and growth. The workflow is compatible with manual, as well as high speed automated microscopic image acquisition, and it is supplemented with an in-house developed macro 'Spheroid_Finder' for open source software Fiji to facilitate rapid automated image analysis. This protocol was used to characterize and quantify spheroid formation and growth of two different hepatic cell lines, hTERT immortalized, but non-cancerous, adult human liver stem cell line HL1-hT1, and human hepatocellular carcinoma cell line HepG2, as well as their responses to a model antiproliferative and cytotoxic agent, 5-fluorouracil. The complete protocol provides a simple and ready-to-use solution to initiate scaffold-free spheroid cultures in any laboratory with standard equipment for mammalian in vitro cell culture work. Thus, it allows to increase throughput and scale of spheroid culture experiments, which can be greatly utilized in different areas of biomedical, pharmaceutical and toxicological research.
Keywords: buněčné sféroidy; Cell Survival; játra; nádory jater; Toxicity Tests; testy toxicity; Drug Screening Assays, Antitumor; Humans; fluoruracil; Antimetabolites, Antineoplastic; průběh práce; rychlé screeningové testy; Time Factors; lidé; Liver Neoplasms; proliferace buněk; Workflow; Hep G2 Cells; časové faktory; Spheroids, Cellular; Stem Cells; Liver; buňky Hep G2; Cell Proliferation; protinádorové antimetabolity; Fluorouracil; screeningové testy protinádorových léčiv; kmenové buňky; buněčné kultury; Cell Culture Techniques; High-Throughput Screening Assays; viabilita buněk; Carcinoma, Hepatocellular; hepatocelulární karcinom